ANALISIS KONSEP MATEMATIKA DALAM WAKTU SALAT WAJIB DAN ZAKAT BERDASARKAN PERSPEKTIF ISLAM - Dian Noer Asyari (LP2M Universitas Ibrahimy, 2021)
The integration of religious and mathematical sciences is essential for enhancing a Muslim’s knowledge in both fields. This study aims to describe mathematical concepts in prayer times and zakat while serving as a reference for students and teachers. Using a qualitative method with a library research approach, this study explores mathematical concepts such as angle relations, number systems, addition, and multiplication found in Islamic practices. The findings highlight the significance of integrating religious and general sciences in education. This approach not only enhances critical thinking skills but also fosters gratitude towards Allah SWT.